OPTIMIZATION OF SOCIAL MEDIA STRATEGIES IN THE ACADEMIC ENVIRONMENT: A CASE STUDY OF INTERNSHIPS IN THE DIGITAL BUSINESS STUDY PROGRAM AT UMSIDA - Aulia Widyasmara, Bunga; Hari Prasojo , Bayu (Antis-Publisher, 2025)
Objective: This study aims to examine the effectiveness of social media strategies in enhancing the image and credibility of the Digital Business Study Program at the University of Muhammadiyah Sidoarjo (UMSIDA), with a focus on promoting the program through social media platforms. Method: A case study approach was employed to analyze the use of social media platforms such as Instagram, Facebook, and TikTok in promoting the program. Data were collected from social media analytics, user engagement metrics, and surveys of students and prospective students to assess the impact on brand awareness, student loyalty, and overall program reputation. Results: The findings show that social media optimization significantly increases audience reach, engagement, and user interaction. Effective use of visual content and responsiveness to user comments enhances the program’s reputation, leading to higher conversions and stronger student loyalty. Novelty: This study introduces a comprehensive approach to social media marketing within the academic environment, highlighting the potential of digital platforms not only for marketing but also for fostering student interest and academic achievement in the modern digital era.